Exploitation of multilayer coatings for infrared surface plasmon resonance fiber sensors - Allsop, Thomas P.; Neal, Ron M.; Mou, Chengbo; Brown, Patrick R.; Saied, Sayah O.; Rehman, Saeed Ur; Kalli, Kyriacos; Webb, David J.; Sullivan, John L.; Mapps, Desmond J.; Bennion, Ian (My University, 2009)
We demonstrate surface plasmon resonance (SPR) fiber devices based upon ultraviolet inscription of a grating-type structure into both single-layered and multilayered thin films deposited on the flat side of a lapped D-shaped fiber. The single-layered devices were fabricated from germanium, while the multilayered ones comprised layers of germanium, silica, and silver. Some of the devices operated in air with high coupling efficiency in excess of 40 dB and an estimated index sensitivity of Δλ/Δn=90 nm from 1 to 1.15 index range, while others provided an index sensitivity of Δλ/Δn=6790 nm for refractive indices from 1.33 to 1.37.
Keywords: Fiber Sensor; Film preparation; Plasmons